The role of Theory of Mind in the transition towards suicidal attempts in youth NSSI: an exploratory pilot study - Orsolini, Laura; Corona, Diana; Cervelli, Alessandro Leonardo; Ribuoli, Enrico; Longo, Giulio; Volpe, Umberto (Frontiers in Psychiatry, 2024)
Non-suicidal self-injury (NSSI) can both precede and co-occur with suicidal attempts (SA).Underlying mechanisms/factors leading to the transition to SA in NSSI youths have been proposed (including the role of social cognition), despite they should be yet confirmed. Therefore, the study aims at exploring the role of the Theory of Mind in the differentiation of a sample of NSSI youngsters (aged 15-24) according to the presence of SA. We divided the sample into 4 groups using the Deliberate Self Harm Inventory (DSHI) and Columbia Suicide Severity Rating Scale (C-SSRS): control group (notNSSInotSA), NSSI without SA (NSSInotSA), NSSI with SA (NSSIplusSA), and SA without NSSI (SAonly). NSSIplusSA patients displayed higher Reading the Mind in the Eyes Test (RMET) scores (indicative of ToM abilities) than both the NSSInotSA (p=0.0016) and SAonly groups (p=0.0198), while SAonly patients showed lower RMET scores compared to the control group (p=0.0214). Multiple regression models used to differentiate NSSInotSA and NSSIplusSA found a significant association between RMET and LOSCS-CSC (Level Of Self-Criticism Scale-Comparative Self-Criticism) (pC=0.0802, pD=0.0016, pG=0.0053). Our findings supported the hypothesis that a hypertrophic affective ToM may possibly be associated with the occurrence of SA in youth NSSI. Further larger and longitudinal studies should confirm these preliminary findings, by exploring all social cognition dimensions.